Comparative Analyses of Capital City Regions by the Example of Budapest, Székesfehérvár, Tatabánya in Hungary and of Paris and Sens in France - Baráth, Gabriella (Discussion Papers, 2012)
The study analyses changes undergoing in the relation system of metropolitan areas and the issues of social and economic relations arising from the restructur¬ing of spatial and regional disparity systems. The changing relations of metropolitan areas and the reconfiguration of spatial disparities are ruled by complex interactions. Their research is very im¬portant as it highlights the necessity of creating a different strategy from the pre¬sent and emphasises the importance of thinking in regional dimensions and of cooperation. The primary objective of the study is investigating the relations of two metropo¬lises situated in a diverse social and economic environment as well as analysing the interrelations of central cities and their urban environment which depend on the impact forces mediated by the central city. The changing relation systems of metropolitan areas, the reconfiguration of regional spatial disparities and their major outcomes are analysed by the examples of Budapest, the capital city of Hungary, and Paris, a Western European capital.